Ekranisasi Novel Winter In Tokyo Karya Ilana Tan dalam Bentuk Film Winter In Tokyo Karya Fajar Bustomi - Khasanah, Zulia Munna; Awaliyah, Sindi; Sajida, Yasmine Adzka; Damanik, Zeinny Permatasari Syaputri; Syahrani, Natasya Fiqih; Yuniawan, Tommi; Neina, Qurrota Ayu (Kajian Bahasa dan Sastra (KABASTRA), 2024)
This research aims to explore the ecranization of the novel "Winter In Tokyo" by Ilana Tan into a film directed by Fajar Bustomi. The research focuses on the forms of storyline, setting, and character ecranization in the transfer from novel to film. The approach used is a qualitative approach with a descriptive method. The descriptive method describes the forms of ecranization manifested in the novel and film "Winter In Tokyo". The primary data sources come from the novel by Ilana Tan and the movie directed by Fajar Bustomi, with data collection involving reading, watching, and note-taking techniques. The results are presented using descriptive analysis techniques with steps involving description, analysis, and conclusion. This study shows that various forms of ecranization, such as additions, subtractions, and changes, affect the final result in the adaptation process of "Winter In Tokyo" from novel to film.